1 Solve the following equations. Match the equation with the correct solution. \( \square \) \( -8+x=3 \) \( x+12=6 \) \( 9 x=-81 \) \( \frac{1}{4} x=3 \) \( \frac{x}{-3}=7 \) \( \square \) \( \qquad \) \( \square \) DRNA A DEOD THE ANSWIR \[ z=9 \] \[ x=-21 \] \( x=-6 \) \( x=12 \) \( z=11 \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
Let’s decode those equations and match them up with their solutions in a fun and easy way! - For the equation \( -8 + x = 3 \), simply add 8 to both sides to reveal that \( x = 11 \). - Next, the equation \( x + 12 = 6 \) can be solved by subtracting 12 from both sides, yielding \( x = -6 \). - Now, take a look at \( 9x = -81 \). Dividing both sides by 9 gives us \( x = -9 \). - In the equation \( \frac{1}{4} x = 3 \), multiplying both sides by 4 reveals that \( x = 12 \). - Lastly, \( \frac{x}{-3} = 7 \) leads us to multiply both sides by -3 resulting in \( x = -21 \). Here’s the match-up: - \( -8 + x = 3 \) → \( z = 11 \) - \( x + 12 = 6 \) → \( x = -6 \) - \( 9x = -81 \) → \( z = 9 \) (but note \( x \) should be the solution) - \( \frac{1}{4} x = 3 \) → \( x = 12 \) - \( \frac{x}{-3} = 7 \) → \( x = -21 \) Remember, always double-check your solutions to avoid any unexpected surprises!